Pengaruh Fasilitas dan Bauranpromosi terhadap Keputusan Berkunjung pada Event Bazaar Jakarta Fest di Medan - Emya Karunia Br. Pelawi; Rismawati Rismawati (JURNAL RISET MANAJEMEN (JURMA), 2024)
Bazaar Jakarta Fest is an event that is open to the public, where everyone has the opportunity to come and enjoy a variety of shopping, culinary and entertainment experiences presented in a lively and lively atmosphere. Held at Center Point Medan, Medan City. There are several factors that influence the decision to visit including facilities and promotion mix. The purpose of this study was to see the effect of facilities and promotion mix on the decision to visit the Jakarta Fest Bazaar. Data collected through questionnaires and observations. Then it will be analyzed using data quality tests, classical assumption tests, multiple linear analysis, coefficient of determination tests and hypothesis testing. The results of the study show that partially the facilities and promotion mix have a positive and significant influence on the decision to visit the Jakarta Fest Bazaar Event. Simultaneously the facilities and promotion mix have a positive and significant effect on the decision to visit and all the variables of the facilities and promotion mix affect the decision to visit by 81.9% and the remaining 18.1% are influenced by other factors not examined in this study.